Accelerating Independent Community Health Through Revitalization of Integrated Health Posts: Percepatan Kesehatan Masyarakat Mandiri Melalui Revitalisasi Posyandu - Nurlailis Saadah; Budi Yulianto; Budi Joko Santosa; Rahayu Sumaningsih (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
This community service activity aims to facilitate Tambakrejo Candirejo Magetan Village, to accelerate village communities realization that are able to recognize, prevent and overcome health problems independently, so that increases health level. The activity is based on the reality of many children who experience growth and development disorders. The reason is not only from the child's factor but also from the parent's ignorance about the causes and how to overcome it. Many mothers do not want to weigh their children because they are embarrassed if their child's weight decreases. In addition, the elderly health condition also needs to be considered because most of the community still considers that elderly people who are sick are common because they are old and do not need serious treatment. This activity is a combination of participatory rural appraisal, community development, persuasion and education models by empowering mothers of toddlers and health cadres, the elderly and elderly cadres. The implementation of activities through training under the guidance of community service workers, village bidan, and village health post nurses supported by the Village Head along with village officials and students. The material provided includes stimulation of early detection of child growth and development interventions, recognizing signs of diabetes mellitus and hypertension and how to handle them. The results of the activities were monitored and followed up by the Head of Tambakrejo Village, the Head of Candirejo Health Center and the Magetan Health Office through village bidan and village health center nurses (ponkesdes).